The encyclopedia of actuarial science - Teugels, J.L.; Ramsey, H. (Інститут математики НАН України, 2006)
We give a short historical survey on why and how the Encyclopedia has emerged. We consider both the editorial and the managerial side of the project. We indicate some of the special features of the work.